2003
DOI: 10.1161/01.cir.0000043240.87526.3f
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Ultrasound Guidance Improves Angiographic and Clinical Outcome of Stent Implantation for Long Coronary Artery Stenoses

Abstract: Background-Long coronary lesions treated with stents have a poor outcome. This study compared the 6-month outcome of stent implantation for long lesions in patients randomized to intravascular ultrasound (IVUS; nϭ73) or angiographic guidance (nϭ71). Methods and Results-Stenoses Ͼ20 mm in length and a reference diameter that permitted a stent diameter Ն3 mm were eligible. Primary end points were 6-month minimal lumen diameter (MLD) and the combined end point of death, myocardial infarction, and target-lesion re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
149
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(161 citation statements)
references
References 41 publications
7
149
2
3
Order By: Relevance
“…Previous studies using bare metal stent showed that IVUS guidance during PCI reduced the rate of in-stent restenosis and the incidence of reintervention. 8,19 One previous study reported the beneficial role of IVUS guidance during PCI on patients who were treated with DES in terms of reducing both stent thrombosis and TLR. 9 Nevertheless, the beneficial effects of IVUS might be uncertain in various study populations or lesion subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using bare metal stent showed that IVUS guidance during PCI reduced the rate of in-stent restenosis and the incidence of reintervention. 8,19 One previous study reported the beneficial role of IVUS guidance during PCI on patients who were treated with DES in terms of reducing both stent thrombosis and TLR. 9 Nevertheless, the beneficial effects of IVUS might be uncertain in various study populations or lesion subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of a diffuse, long, coronary artery lesion with overlapping BMS is associated with high rates of restenosis [1][2][3] whereas the use of DES greatly attenuates neointimal proliferation, so that in patients with a diffuse, long, coronary lesion, implantation of multiple overlapping DES has been associated with a good clinical outcome. 9 Corp, Natick, MA, USA).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In particular, the implantation of multiple, overlapping, bare metal stents (BMS) has a high restenosis rate. 4,5 Use of drug-eluting stents (DES) results in a significant and sustained suppression of neointimal proliferation, and has greatly attenuated the relationship between stent length and restenosis rate.…”
mentioning
confidence: 99%
“…[8][9][10] We believe the IVUS-guided improvement in the angiographic MLD was the mechanism responsible for the reduced restenosis, reduced repeat revascularization, and reduced MACE. The DIPO study 11) and the TULIP study 12) also suggested that IVUS-guided PCI could reduce restenosis and MACE. However, the OPTICUS study 13) did not show an effect of IVUS guidance on restenosis.…”
Section: Discussionmentioning
confidence: 99%